Body weight trajectories from midlife are associated with cognitive decline in advanced age - Chiara Ceolin; Federica Prinelli; Caterina Trevisan; Adele Ravelli; Silvia Conti; Lorraine Brennan; Lisette C. P. G. M. de Groot; Claire T. McEvoy; Stefania Maggi; Giuseppe Sergi; Marianna Noale; the PROMED-COG Consortium (Scientific Reports)
Abstract Fluctuations in body weight may impact cognitive decline, but current evidence is inconclusive. The aim of this study is to investigate associations between body weight trajectories from midlife to later life and cognitive decline. This retrospective study analyzed harmonized data from two population-based longitudinal studies, the Progetto Veneto Anziani and the Italian Longitudinal Study of Aging, encompassing baseline and two follow-up assessments over 9 years. Weight changes were recorded from baseline to the last available follow-up or from 50 years (self-reported data) to the last available follow-up. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), and cognitive decline was defined as experiencing a MMSE change from baseline to the follow-up within the lowest quartile of the change distribution in the total sample. In a sample of 3852 individuals (46% females, age 65–96 years at baseline), we investigated the impact of weight change on cognitive decline with two sets of analyses. First, using weight measurements obtained during old age, growth mixture modelling identified three weight trajectories: decreasing, stable, and increasing. None of these trajectories was significantly associated with cognitive decline. Second, we considered weight at age 50 as the baseline assessment to capture weight changes from midlife. Among the three trajectories detected (increasing, stable, and decreasing), the decreasing trajectory was significantly associated with a higher likelihood of cognitive decline in males (HR 1.44, 95% CI 1.06–1.94) and females (HR = 1.37, 95%CI 1.23–1.67), whereas the increasing trajectory was associated with cognitive decline only in females (HR = 1.33, 95%CI 1.01–1.76). These results suggest that changes in body weight from middle to older age are associated with cognitive decline in advanced age. Since body weight is influenced by multiple factors, a broader assessment of health—including metabolic, vascular, behavioral, and social dimensions—should be considered in both research and clinical settings.